Epidemic profile of COVID-19 child deaths in Sri Lanka: a retrospective nationwide analysis - Kapila Jayaratne; Poojani Illangasinghe; Suvini Wanniarachchi; Dilka Hettiarachchi; Chithramalee de Silva; Guwani Liyanage (BMC Pediatrics)
Abstract Introduction Understanding the impact of the COVID-19 pandemic on child survival is crucial. Analysing COVID-19-related child deaths, even years after the pandemic, is critical for informing future pandemic preparedness and response efforts. Methods We conducted an analysis of all "SARS-CoV-2/COVID-19 positive deaths" among children and adolescents (aged < 18 years) recorded through a purposefully designed Child Death Surveillance and Response System (CDSRS) from October 2020 to September 2022. It included all deaths with a positive SARS-CoV-2. The analysis involved a thorough review of documents (bedhead tickets, field/institutional investigation and postmortem examination reports, and compiled case scenarios). Multivariable backward logistic regression was conducted to identify risk factors associated with deaths attributed to COVID-19 infection. Additionally, a comparison of socio-demographic characteristics was conducted between deaths due to all causes and those attributed to COVID-19 infection. Results A total of 111 deaths with a positive SARS-CoV-2 test were analyzed. Among these, 81 deaths (73%) were categorized as directly attributed to COVID-19 infection. Fourteen children (17.2%) had Multisystem Inflammatory Syndrome. Cardiovascular disease was the most common comorbidity (28.4%). The odds of deaths attributed to COVID-19 infection were eleven times higher with chronic diseases compared to incidental SARS-CoV-2 positive test (OR:11.22, 95% CI:1.735, 72.496). Tamil ethnicity appeared to be protective when compared to the Sinhalese (OR:0.07, 95% CI: 0.008, 0.598). The model explained 44.8% of the variance. When compared to national all-cause mortality data, females (p = 0.03), post-neonatal infants (p < 0.001), and > 5–18 years (p = 0.005) were identified as being at higher risk of death due to COVID-19 infection. Conclusion The proportion of COVID-19-positive deaths during the study period was higher than that reported in high-income countries, with most deaths directly attributed to SARS-CoV-2. Higher mortality rates were observed among post-neonatal infants, children over five years, females, those with Sinhalese ethnicity, and pre-existing chronic medical conditions, particularly cardiovascular disease.